Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s10533-019-00547-8
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen emissions: an overlooked key component of the N balance of montane grasslands

Abstract: While emissions of nitric oxide (NO), ammonia (NH 3) and nitrous oxide (N 2 O) from grassland soils have been increasingly well constrained, soil dinitrogen (N 2) emissions are poorly understood. However, N 2 losses might dominate total gaseous nitrogen (N) losses. Knowledge on N losses is key for the development of climate-adapted management that balances agronomic and environmental needs. Hence, we quantified all gaseous N losses from a montane grassland in Southern Germany both for ambient climatic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 64 publications
1
22
1
Order By: Relevance
“…With a potential loss of up to half of slurry N application, a potential maximal N 2 loss of 16 kg N ha −1 appears possible at a moderate autumn slurry addition of 36 kg N ha −1 followed by intense FTCs. This share of slurry-N lost by N 2 within 3 FTCs is slightly higher than the N 2 loss of 31-42% that was detected within 2 weeks in a laboratory experiment simulating a surface slurry addition (of 50 kg N ha −1 ) to the soil of this study in summer under incubation conditions of 70% WFPS and 18°C (Zistl-Schlingmann et al 2019). Despite transferability of our findings to field conditions remain limited, our findings imply that the farmers' practice of applying slurry late in autumn could involve the risk of limited N use efficiency when there are several severe FTC in the subsequent winter.…”
Section: Effect Of Fertilization On N 2 O and N 2 Fluxes During Ftcscontrasting
confidence: 60%
See 1 more Smart Citation
“…With a potential loss of up to half of slurry N application, a potential maximal N 2 loss of 16 kg N ha −1 appears possible at a moderate autumn slurry addition of 36 kg N ha −1 followed by intense FTCs. This share of slurry-N lost by N 2 within 3 FTCs is slightly higher than the N 2 loss of 31-42% that was detected within 2 weeks in a laboratory experiment simulating a surface slurry addition (of 50 kg N ha −1 ) to the soil of this study in summer under incubation conditions of 70% WFPS and 18°C (Zistl-Schlingmann et al 2019). Despite transferability of our findings to field conditions remain limited, our findings imply that the farmers' practice of applying slurry late in autumn could involve the risk of limited N use efficiency when there are several severe FTC in the subsequent winter.…”
Section: Effect Of Fertilization On N 2 O and N 2 Fluxes During Ftcscontrasting
confidence: 60%
“…Hence, our findings on FTC N 2 emissions are generally in line with the very limited earlier work on that topic. Moreover, for the soils of this study, Zistl-Schlingmann et al (2019) reported N 2 emissions from intact-plant soil mesocosms of up to 2-4.5 mg N 2 -N m −2 h −1 after heavy summer precipitation events. This is in the same order of magnitude as the FTC N 2 emissions from disturbed soil of ca 1-2.5 mg N m −2 h −1 .…”
Section: Effect Of Soil Moisture and Temperature On N 2 O And N 2 Flumentioning
confidence: 51%
“…This finding is further strengthened by the low N leaching rates (1-5 kg ha −1 year −1 ) reported by [20] for the same lysimeters. Instead, the high proportion of unrecovered 15 N indicates high direct losses from slurry along gaseous pathways as indicated by the direct measurements of [54].…”
Section: Effects Of Intensificationmentioning
confidence: 99%
“…The emission of dinitrogen (N 2 ) from soil denitrification is considered to be a major gaseous N loss pathway particularly in flooded paddy fields, where the strictly anaerobic environment promotes the complete reduction of nitrate or nitrite to N 2 , through the intermediates of nitrous oxide (N 2 O) and nitric oxide (NO; Butterbach‐Bahl, Baggs, Dannenmann, Kiese, & Zechmeister‐Boltenstern, ; Davidson & Verchot, ). Quantifying N 2 emissions from flooded paddy fields is therefore an essential prerequisite for the development of improved N management to increase fertilizer N use efficiency (Wang et al, ; Zistl‐Schlingmann et al, ). In addition to N 2 emission, ammonia (NH 3 ) emission is another major gaseous N loss pathway in paddy fields, which, in contrast to N 2 emissions, has been well studied during the past two decades (Xia, Lam, et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%